Radical Surgery in Advanced Cervical Cancer Patients Receiving Bevacizumab-Containing Chemotherapy: A "Real Life Experience". Issue 8 (1st October 2018) - Fagotti, Anna; Conte, Carmine; Stollagli, Francesca; Gallotta, Valerio; Salutari, Vanda; Bottoni, Carolina; Bruno, Matteo; Zannoni, Gian Franco; Scambia, Giovanni
Abstract : Background: Platinum-based chemotherapy plus bevacizumab is the new standard of care in stage IVB cervical cancer (CC) patients. In this new scenario, radical surgery could be offered in selected cases with an optimal clinical response. Potential surgical complications related to previous bevacizumab treatment have never been described before in this type of setting. Methods: This is a single-institutional retrospective study on women with CC who received radical pelvic surgery after platinum-based chemotherapy (platinum-taxol) plus bevacizumab. Results: Between April 2016 and September 2017, 15 patients with CC underwent radical surgery after bevacizumab-containing chemotherapy (platinum-taxol) at the Division of Gynecologic Oncology, Catholic University of the Sacred Heart in Rome, Italy. All patients received at least 3 cycles of treatment. Fourteen (93.4%) patients underwent radical hysterectomy, whereas 1 patient received pelvic anterior exenteration. Median operating time was 290 minutes (range, 220–400), and estimated blood loss was 250 mL (range, 50–1500). Median time of hospitalization was 5 days (range, 2–21). Pathological response in the cervix was complete in 3 cases and microscopic in 1 patient (26.7%). Intraoperative complications occurred in 3 cases: 2 vascular injuries and 1 ureteral injury. Three patients (20.0% of the whole series) experienced grade 3 complications. At last follow-up (median time, 9 months), the median overall survival is 13 months (range, 6–31): 7 (46.7%) women were free of disease, 8 (53.3%) patients progressed, and 3 of them died of disease. Conclusions: Radical surgery can be performed in women with CC previously treated with a bevacizumab-containing regimen.